Posterolateral Corner Reconstruction Using Double Femoral Fixation With Adjustable Loop Cortical Suspension and Interference Screw - Nicholas I. Kennedy MD; Erik Therrien MD; Robert G. Marx MD; Michael J. Stuart MD; Bruce A. Levy MD (SAGE Publishing, 2022)
Background: The posterolateral corner (PLC) of the knee is a complex anatomic region of the knee comprising the popliteus tendon, the popliteofibular ligament (PFL), and the fibular collateral ligament (FCL). Treatment of PLC injuries is based on the degree of varus and rotational instability on preoperative examination and is recommended in grade 3 injuries. 1,6 Technique Description: The key concept of this new surgical technique is to use adjustable loop cortical suspensory fixation implants for initial femoral fixation of the popliteus and the FCL grafts. This allows for individual tensioning of the grafts prior to definitive fixation with an interference screw. An anatomic fibular tunnel is initially created, followed by popliteus and FCL anatomic femoral socket drilling. A TightRope RT implant is attached to the popliteus end of the graft and secured through a bone tunnel on the medial femoral cortex initially. The popliteus end of the graft is then pulled into the femoral socket before tunneling the graft through the fibular tunnel. A second TightRope RT implant is secured to the FCL end of the graft before securing it to the medial femoral cortex through a bone tunnel and pulling the graft into the drilled femoral socket. An interference screw is first used to secure the graft at the fibular tunnel. The knee is then taken to 60° where the TightRope device is used to remove residual creep and optimize final tensioning prior to final fixation with interference screw in femoral socket. With the knee at 30° of flexion, neutral rotation, and slight valgus, the same steps are repeated for FCL graft. A posterolateral capsular shift is completed for additional stability. Results: Residual posterolateral corner instability or failure after reconstruction surgery has been reported in 6% to 9.4% of surgical reconstruction case. 2,3,5 The use of cortical suspensory devices in PLC reconstructions allows independent dialing of optimal graft tension for both the popliteus and FCL reconstruction before final interference screw fixation, therefore presumably limiting any residual creep and allowing for a double femoral fixation of the graft. Discussion: We describe a novel technique for posterolateral corner reconstruction which allows for optimal and individual tensioning of the structures of the posterolateral corner. Given the technique still uses well-described and validated graft choices and anatomic landmarks for reconstruction, we expect this new technique to allow for similar if not improved outcomes when compared with current gold standard. 4